(3JdNjU TQM aUhd CHh bQGWs - (3Ydj Hf jhSa Hf UOQI GdQLi TQa GdOjfs; (3GHf CHj UGOb , YHO GdQMef Hf Ydj Hf CMeO Hf CHj UGOb, CHh GdbGSe (B- (3HbQGW GdKGfj GdfjSGHhQj,J (B470 (3g` ? s ((3MSf Hf YjSi GdGfbQHi GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg echf GdCchGf hTQa GdEfSGf CeG HYO aEf cJGH GdaUhd dhGdO GdCWHGA CHh bQGW CaVd GdcJH GdWHjI dGTJeGdg Ydi bhGfjf YdejI hYedjI s
(3BNQgG (B:s
(3hCeG GdaUhd GdeOdSI hGdecQQI aJQcfG PcQgG TabI Ydi ahJ GdReGf ajeG dG jLOi faYkG hGddg hdi GdNjQ hgh MSHfG hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3hQO GdYfhGf GdCUdi ai (B: (3cX (B2 / 1268s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B154s
Keywords: (3GdWHs